Paradise or dark side: How does metaverse experience shape the perspectives of pre-service teachers? - Avinç, Ece; Doğan, Fatih (Journal of Interdisciplinary Studies in Education, 2025)
This study explores how introducing the metaverse to pre-service science teachers without prior virtual experience impacts their perceptions. Initially, semi-structured pre-interviews revealed that participants associated the metaverse with terms like "imaginary," "virtual universe," and "expensive." Following a detailed presentation covering the metaverse’s definition, history, applications, and interdisciplinary potential, participants experienced it firsthand using 3D glasses. Post-experience interviews showed a notable shift in perceptions, with terms like "education," "communication," and "health" emerging. Teachers who initially viewed the metaverse negatively became more open to its use in education and other fields. The study concludes that even brief exposure to the metaverse can significantly broaden perspectives and foster more positive attitudes toward its potential applications.